"We feel left out": Experiences of social inclusion from the perspective of young adults with intellectual disability. Issue 1 (2nd January 2019) - Merrells, Jessica; Buchanan, Angus; Waters, Rebecca
ABSTRACT: Background: Few studies discuss social inclusion from the voice and perspective of young adults with intellectual disability who have been lifelong recipients of individualised community-based coordination and services focusing on inclusion and participation. It is important to understand the perspective of people with an intellectual disability how they experience and perceive social inclusion within their own lives. Method: Ten participants aged 18 to 24 years diagnosed with intellectual disability living in the community alone, or with their family, participated. All received long-term individualised community-based coordination and services. They were interviewed about how they spend their time, form relationships, and feel included. A phenomenological approach was used with a thematic analysis to form codes from transcripts into two major themes. Results: Young adults within this study experienced feelings of segregation and exclusion from community. Participants experienced trouble finding employment and were frequently bored. Social interactions were mainly with family and others with a disability in formal programs. Conclusions: Despite being long-term recipients of individualised community-based coordination the young adults discussed significant experiences of segregation and exclusion impacting negatively on their lives.